Activity of serum creatine kinase, lactate dehydrogenase and LD isoenzymes in piglets affected with congenital tremor: a case report - Tomko, M (Acta veterinaria Hungarica, 1992)
The activities of serum creatine kinase (CK), lactate dehydrogenase (LD) and LD isoenzymes were studied in 14 Prestice black pied pigs from a herd affected with congenital tremor. Mean CK activity was 19.57 +/- 3.56 mu kat.l-1 for 6 adult pigs, and it was 21.03 +/- 1.33 mu kat.l-1 and 20.42 +/- 1.23 mu kat.l-1 for the affected (n = 5) and control (n = 3) piglets, respectively. No significant differences were demonstrable between the groups in CK activity. Total serum LD and LD-4 as well as LD-5 isoenzyme activities were higher in sows. Piglets affected with congenital tremor showed an increase in total LD enzyme and LD-5 isoenzyme activity. It is concluded that no relationship exists between congenital tremor and serum CK activity in piglets. At the same time, there is a positive relationship between congenital tremor and significantly (P < 0.01) elevated LD enzyme and LD-5 isoenzyme activity. The results allow us to suggest that total lactate dehydrogenase and LD-5 isoenzyme activities could be used as biological markers of congenital tremor in piglets.
Keywords: Swine; ženské pohlaví; Clinical Enzyme Tests; Creatine Kinase; nemoci prasat; prasata; Isoenzymes; Tremor; izoenzymy; kreatinkinasa; Swine Diseases; Animals; klinické enzymatické testy; tremor; zvířata; mužské pohlaví; Male; L-laktátdehydrogenasa; Female; L-Lactate Dehydrogenase